Armeria x cintrana nothoespecie nova para o género Armeria Willd. (Plumbaginaceae) - Tauleigne-Gomes, Cristina (Acta Botanica Malacitana, 2011)
Armeria x cintrana a new nothoespecies in genus Armeria Willd. (Plumbaginaceae) Palavres chave. Armeria, Plumbaginaceae, Híbrido, Estremadura, Portugal. Key words. Armeria, Plumbaginaceae, Hybrid, Estremadura, Portugal.